PREVALENCE OF THUMB PAIN IN PHYSIOTHERAPISTS OF PESHAWAR - Abidin, Syed Zain Ul; Bukhari, Sara; Zeb, Alam; Farooqi, Salman (Annals of Allied Health Sciences, 2020)
OBJECTIVE: To determine the prevalence of thumb pain in physiotherapists of Peshawar. METHODS: A cross sectional study was conducted at different physical therapy clinical set ups of Peshawar. To collect data from the concern participants, 100 questionnaires were distributed using convenience sampling. 93 participants responded positively, in which 62 were male and 31 were female. Visual analog scale (VAS) was used to measure the pain. SPSS version 20 was used for data analysis. RESULTS: Results showed that 78(83.9%) subjects have thumb pain while 15(16.1%) do not experience thumb pain. According to pain in hand distribution shows that 39(41.9%) were those who have pain in their right thumb while 16(17.2%) were those who have pain in their left thumb and 23(24.7%) were those who have pain in their both thumbs. CONCLUSION: The prevalence of thumb problems in physiotherapists appears to be high and can be of sufficient severity to impact on careers.